การวิเคราะห์สถานการณ์การป้องกันการเกิดแผลกดทับในผู้ป่วยสูงอายุ บาดเจ็บสมองที่ได้รับการผ่าตัด หอผู้ป่วยศัลยกรรมชาย โรงพยาบาลลำพูน - ศศิธร พิชัยพงศ์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
Pressure sores among postoperativeelderly patients with traumatic brain injuryisan importantproblem that can havephysiological,spiritual, and socialimpacts.Theobjective of this study was to conduct a situational analysisof pressure sores prevention among postoperative elderly patients with traumatic brain injury in the Male Surgical Ward ofLamphun Hospital based on the framework of Donabedian’squality of caredevelopmentwhich include the domains of structure, process, and outcome. The sample was purposively selected from 3 populations including:1) 3 administratorsincluding thehospital director, head nurse of the surgical unit, and head nurse of male surgical ward; 2) 12 service providersincluding 6 nurses, 3 nurse aids, 1 physician, 1 nutritionist, and 1 physical therapist; and 3) 5 elderly patients and 5 caregivers. The instruments used for collecting data were: 1)demographic data recording form,2) in-depth interview guideline; and 3) pressure ulcer prevention knowledge test. Data were analyzed using descriptive statistics and content analysisbased on the framework. The results of this study revealed the following: 1. Structure: Apolicy for care andprevention of pressure sores that includedspecific factors and development pattern of care was already in place.Aspecific care team for elderly patients existed but there was no specific team for pressure sore care.A health care team had support for developing research and training on pressure sore prevention.There was insufficient medical equipment.There was no specific budget for pressure sores. 2. Process: there was a guideline for pressure sorepreventiondeveloped6 years ago and was not updated. Continuous care based onthis guideline was not provided because there was not enough time. Caregivershad low participation in discharge planning. 3. Outcome: The incidence of pressure soreshad not decreased in the hospital. Caregivers had mild to moderate levels of pressure sore prevention knowledge and understanding. Care providers had moderate levels of pressure sore prevention knowledge and understanding. The findingsfromthis study could serve as guidelines for developingquality of care for postoperative elderly patients with traumatic brain injury in the MaleSurgicalWardofLamphunHospital.